PENGARUH KREATIVITAS BELAJAR DAN EFIKASI DIRI TERHADAP PRESTASI AFEKTIF MELALUI MOTIVASI BERPRESTASI (Studi kasus pada Madrasah MTs Pembangunan UIN Jakarta) - Wahyudi . (Prodi Manajemen Fakultas Ekonomi Universitas Pamulang, 2014)
STRUCTUR EQUATION MODEL ANALYSIS THE EFFECT LEARN CREATIVITY AND SELF EFFICACY ON STUDENTS AFFECTIVE ACHIEVEMENT THROUGH REACH MOTIVATION (empirical studies in MTs. Madrasah Pembangunan). The study attempted to examine a phenomena and to gain empirical evident, as well as to get a brief data on the influence of learn creativity and self-efficacy on students affective achievement through reach motivation. The study applied descriptive and inductive method it’s include 171 respondents as the samples. The samples were selected through Purposive sampling. The structural equation model was also used as the means to examine the data. The findings could be concluded as follows: (1) There was positive effect from all independent variables to affective achievement within value influence 6,6%. (2) The results of this research indicated that self-efficacy was the greatest affecting to the achievement motivation was as much as 43%, meanwhile coefficient learn creativity was 7,9%. And simultaneously both have a positive influence as much as 19% on reach motivation. (4) There are positive influence of learn creativity and self-efficacy on affective achievement through motivation was equal to 28%. The result suggested, to reach students affective behavior should be encouraged constantly in order to be stable and to gain a constant synergy from all sides involved in education institution, whether it is from internal or external. Keywords: Learn Creativity, Self Efficacy, Reach Motivation and Students Affective Achievement